Critical factors in the anodic formation of extremely ordered titania nanocavities - Yoo, Jeong Eun; Schmuki, Patrik (Journal of The Electrochemical Society, 2019)
In the present work, we discuss the formation of a highly ordered form of TiO2 nanotubes (U-tubes) which are grown by anodizing Ti metal in a concentrated HF/H3PO4 electrolyte. The crucial parameters determining geometry and order of the tubes (such as, temperature, applied voltage, concentration of HF, and anodizing time) are investigated and discussed. Under optimized conditions, not only very high degree of order, but also a perfectly open tube top morphology is obtained. The amorphous titania tubes (cavities) consist of a phosphate rich inner layer and a fluoride rich outer layer. Thermal crystallization of these short amorphous cavities to anatase/rutile at temperatures (>400°C) in air leads to partial oxidation of the underneath metal - this and the short length of the tubes, usually around 200 nm, pose challenges for potential photoelectrochemical applications. However, the limited tube length can be overcome by a double anodizing technique. The extremely high order and unique nature of these types of self-ordered tubes allows for unprecedented control and enables various uses of the tubes.
CRIS-Team Scopus Importer:2019-10-25